2008
DOI: 10.1080/09650790802260372
|View full text |Cite
|
Sign up to set email alerts
|

Initiating education reform through lesson study at a university in Indonesia

Abstract: This paper analyses the issues involved in promoting lesson study in an Indonesian university, based on a case study of the Faculty of Mathematics and Science (FMIPA) of the State University of Yogyakarta. Five points are discussed. First, conducting lesson study with schools revealed that the faculty managers noticed the ignorance about lesson study in FMIPA and decided to conduct lesson study by themselves to learn more. Second, despite using a didactic teaching approach initially, more faculty members began… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…Regarding the benefits of implementing the lesson study in higher education, several international studies have been examined in Mathematics (McMahon & Hines, 2008;Parks, 2008;Post & Varoz, 2008;Saito, Hawe, Hadiprawiroc & Empedhe, 2008;Chassels & Melville, 2009;Matthews, Hlas & Finken, 2009;Burroughs & Luebeck, 2010;Fernandez, 2010;Elipane, 2011;Lucas, 2014;Thompson, 2015;Leavy & Hourigan, 2016), Physics (Saito et al, 2008;Hamzeh, 2014;Juhler, 2018), Chemistry (Saito et al, 2008), Biology (Saito et al, 2008;Hamzeh, 2014),Writing (Parks, 2009), Science (McDowell, 2010;Carrier, 2011;Pongsason, Akerson, Rogers & Weiland, 2011;Thompson, 2015), Geography and Modern Languages (Cajkler, Wood, Norton and Pedder, 2013), Technology (Thompson, 2015), Engineering (Thompson, 2015), English as a foreign language (Angelini & Alvarez, 2018) and Language Courses (Lucas, 2014). In Greece, a smaller number of researches was found, examining the benefits of implementing the lesson study in higher education in Teaching Practice (Rekalidou et al, 2014), the Project method (Giannakidou et al, 2013) and Physical Education (Dania et al, 2013).…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the benefits of implementing the lesson study in higher education, several international studies have been examined in Mathematics (McMahon & Hines, 2008;Parks, 2008;Post & Varoz, 2008;Saito, Hawe, Hadiprawiroc & Empedhe, 2008;Chassels & Melville, 2009;Matthews, Hlas & Finken, 2009;Burroughs & Luebeck, 2010;Fernandez, 2010;Elipane, 2011;Lucas, 2014;Thompson, 2015;Leavy & Hourigan, 2016), Physics (Saito et al, 2008;Hamzeh, 2014;Juhler, 2018), Chemistry (Saito et al, 2008), Biology (Saito et al, 2008;Hamzeh, 2014),Writing (Parks, 2009), Science (McDowell, 2010;Carrier, 2011;Pongsason, Akerson, Rogers & Weiland, 2011;Thompson, 2015), Geography and Modern Languages (Cajkler, Wood, Norton and Pedder, 2013), Technology (Thompson, 2015), Engineering (Thompson, 2015), English as a foreign language (Angelini & Alvarez, 2018) and Language Courses (Lucas, 2014). In Greece, a smaller number of researches was found, examining the benefits of implementing the lesson study in higher education in Teaching Practice (Rekalidou et al, 2014), the Project method (Giannakidou et al, 2013) and Physical Education (Dania et al, 2013).…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…Regarding the conditions and procedures for the effective implementation of the lesson study in higher education, only five international studies have been examined in Mathematics (Saito et al, 2008;Molina, 2012;Wessels, 2018), Physics (Saito et al, 2008), Chemistry (Saito et al, 2008), Biology (Saito et al, 2008) and Science (McDowell, 2010;Carrier, 2011) and none in Greece. The most important prerequisites for the effective implementation of the lesson study are the reflection of the preservice teachers who develop their knowledge, skills and willingness to use it in their teaching, the participation and cooperation of teachers, the creative presence of the mentor, policy support from teacher educators who encourage teachers to develop and maintain quality teaching.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…The teaching and observation phase existed of the research lesson in which one of the supervisors was having the supervision meeting with the selected case student while the others observed the meeting and made notes with a focus on student learning (Dudley 2013;Saito et al 2008). Next to the room in which the research lesson was delivered, the other three supervisors and the lesson study facilitator were sitting in the observation room.…”
Section: Teaching and Observation Phasementioning
confidence: 99%
“…They also use teamwork in their lessons, increasing student interest in learning and developing closer relationships with them. In spite of the emphasis on the importance of observing the learning reality of students, the teaching staff focuses on teaching methodology and enriches its experience and learning (Saito et al, 2008;Cajkler et al, 2013). The development of more positive beliefs and attitudes of preservice teachers and their trainers as a result of the implementation of the lesson study is demonstrated by other researchers (Lewis & Hurd, 2011;Darling-Hammond & Richardson, 2009).…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…In addition, regarding the attitudes and beliefs for the lesson study of teacher educators in higher education, a smaller number of researches were examined internationally in Mathematics (Post & Varoz, 2008;Saito et al, 2008), Physics, Chemistry and Biology (Saito et al, 2008) and Geography and Modern Languages (Cajkler et al, 2013). Also, it is worth noting that Greece has not studied any research.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%